TINJAUAN PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA PENCABULAN ANAK DALAM PUTUSAN NOMOR 56/PID.SUS/2023/PN WNG - Rhevika Gurindra Hapsari; Bambang Santoso (Sebelas Maret University, 2024)
This article analyzes criminal procedural law related to the suitability of the judge's considerations in deciding the case of the crime of child molestation in Verdict Number 56/Pid.Sus/2023/PN Wng with Article 183 of the Criminal Procedure Code. The purpose of this article is to prove whether the judge's considerations in deciding the case of child molestation in Verdict Number 56/Pid.Sus/2023/PN Wng are in accordance with Article 183 of the Criminal Procedure Code. The research method used is normative legal research. This research is prescriptive and applied. The method for collecting legal materials is by means of literature study and the legal materials used are primary legal materials and secondary legal materials. Based on the results of research and discussions to answer this problem, it can be concluded that the judge's consideration in deciding the case of child molestation in Verdict Number 56/Pid.Sus/2023/PN Wng is in accordance with Article 183 of the Criminal Procedure Code. This is because the judge's consideration in deciding the case contained 3 pieces of evidence, namely Witness Statement, Defendant's Statement and Letter (visum et repertum number: 445.1/06757).